2020
DOI: 10.1534/g3.120.401196
|View full text |Cite
|
Sign up to set email alerts
|

Selective Loss of Diversity in Doubled-Haploid Lines from European Maize Landraces

Abstract: Maize landraces are well adapted to their local environments and present valuable sources of genetic diversity for breeding and conservation. But the maintenance of open-pollinated landraces in ex-situ programs is challenging, as regeneration of seed can often lead to inbreeding depression and the loss of diversity due to genetic drift. Recent reports suggest that the production of doubled-haploid (DH) lines from landraces may serve as a convenient means to preserve genetic d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…The authors stated that obtaining the DHL did not result in systematic directional selection in specific genomic regions. However, using the same genomic data, Zeitler et al (2020) obtained contradictory results; that is, there was a restriction in the variability when was used.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors stated that obtaining the DHL did not result in systematic directional selection in specific genomic regions. However, using the same genomic data, Zeitler et al (2020) obtained contradictory results; that is, there was a restriction in the variability when was used.…”
Section: Resultsmentioning
confidence: 99%
“…There are no reports in the literature on whether the constitution of DHL differs from that of lines obtained using conventional inbreeding methods. Melchinger et al (2017) evaluated DHL with single-nucleotide polymorphism (SNP) markers on corn and did not detect any restriction in its genetic variability, whereas Zeitler et al (2020) used the same genomic data to observe losses in DH variability. In some crops, such as triticale, barley, and corn, the performance of the lines obtained via DH and a conventional method, was not similar (Charmet and Branlard 1985, Bjornstad et al 1992, Ma et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…It is important to note that our line panel included many old lines that have made only a limited contribution, if any, to commercial F1 hybrids or recent breeding pools. Our panel therefore certainly overestimates the genetic diversity present in the germplasm of modern breeding inbred lines (Zeitler et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, SNPs from 50 K arrays were previously identified in 27 lines (Gore et al ., 2009). These SNPs may not reflect well the total genetic diversity of landraces, as certain specific landrace haplotypes may not have been transmitted to first cycle lines due to their deleterious effect at the homozygous state (inbreeding depression) or gamete sampling (drift) (Zeitler et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the low population structure and rapid decrease of linkage disequilibrium within populations of DH lines landraces, these would be an ideal tool for association mapping. However, Zeitler et al (2020) reported that landrace DH lines may result in a decreased genetic diversity.…”
Section: Landraces and Diversity Inclusionmentioning
confidence: 99%